Local Financial Development and the Aid-Growth Relationship - Nkusu, Mwanza (IMF Working Papers; Working Paper ;, 2004)
With official development assistance (ODA) set to rise as countries strive to meet the Millennium Development Goals (MDGs), aid effectiveness remains an important area of development policy. An increasing number of studies support the notion that ODA can contribute to growth in a nonlinear relationship. In this paper, we investigate a new hypothesis regarding this relationship: that deeper financial markets in aid-recipient countries facilitate the management of aid flows, thereby enhancing aid effectiveness. An empirical analysis, using a panel data set, finds robust support for the hypothesis.